2022
DOI: 10.1007/s00784-022-04729-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sugar-free polyol chewing gums on gingival inflammation: a systematic review

Abstract: Objectives A systematic review of published data was conducted with the aim of assessing the effects of sugar-free polyol chewing gums on gingival inflammation. Materials and methods Electronic and hand searches were performed to find clinical studies concerning the effects of sugar-free chewing gums on gingival scores. Prospective randomized controlled clinical trials published between 1971 and 2021 were included in the review. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Notably, the sugar-free gums (groups 2 and 3) elicited higher muscle activity compared to the sugar-containing gum types (groups 1 and 4) and the control. The sugar-free chewing gums not only reduced plaque quantity and gingival inflammation but also had a positive impact on the chewing cycle [ 17 ]. The evidence suggests that sugar-free chewing gum has a caries-reducing effect, possibly due to saliva stimulation, a lack of sucrose, and the inability of bacteria to metabolize polyols into acids [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the sugar-free gums (groups 2 and 3) elicited higher muscle activity compared to the sugar-containing gum types (groups 1 and 4) and the control. The sugar-free chewing gums not only reduced plaque quantity and gingival inflammation but also had a positive impact on the chewing cycle [ 17 ]. The evidence suggests that sugar-free chewing gum has a caries-reducing effect, possibly due to saliva stimulation, a lack of sucrose, and the inability of bacteria to metabolize polyols into acids [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The various benefits of erythritol have been reported in the dental–oral field. Experiments using rats have reported that erythritol is not utilized by Streptococcus mutans , which are caries-causing bacteria in the oral cavity, and it does not cause dental caries itself [ 45 ]. In vitro experiments have shown that, like xylitol, erythritol inhibits the growth of S. mutans and the formation of biofilms [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sugar-free gum is chewing gum that uses a sweetener instead of sugar. Popular sweeteners such as xylitol, sorbitol, and mannitol [5]. The general composition of chewing gum includes sweetener (50-65%), gum base (18-30%), corn syrup (12-20%), color and flavor (1-2%), and softeners (0.3-3%).…”
Section: Sugar-free Chewing Gum and Oral Healthmentioning
confidence: 99%